Analisis Perubahan Tutupan Lahan dari Citra TerraSAR-X Menggunakan Metode Analisis Texture dan Segmentasi di Jakarta - Dyatmika, Haris Suka; Sari, Inggit Lolita; Muchsin, Fadila; Indriasari, Novie; Budiono, Marendra Eko (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2020)
Rapid urban growth in Jakarta is indicated by the increases of building area, such as settlements, roads, commercial and others. Identification of land cover extent and its changes is a vital data for urban planning. One method for land cover mapping and its changes is obtained by the utilization of remote sensing data that characterize as having a continuity data, covers a vast area, and cost-effective. Remote sensing data can be obtained from optical and radar imagery. Radar data importance for mapping land cover and land cover changes because radar data does not constrain by time and weather. In early 2018, the TerraSAR-X (TSX) data can be acquired at the LAPAN Parepare ground station. This research uses the TSX Stripmap image mode with a spatial resolution of 3 m in 2010 and 2013. The TSX data will be used to map the land cover and land cover changes in Jakarta using method of the texture analysis and image segmentation. The accuracy assessment of the map will be assessed visually and quantitatively using the Pleiades images (0.5 m) and Google Earth images. The results show that the TSX images detect the current developments of settlements, new roads construction and provide information on the loss of green open space in Jakarta.